Proponents of gay marriage listening to speaker - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows the back of a speaker at a podium talking to a group of demonstrators outside the Santa Clara County government services building at Day of Marriage demonstration. The demonstrators hold signs that read, "Lo[ve] is love", "Love does not discriminate", "State [not equal to] Church", "Marriage is a civil rite", "Love deserv[es] marriage", and "Marriage is a [fa]mily [val]ue". Reverend Vaughn Beckman is standing at the far right in the front row. He is wearing dark clothing and a collar.